1999
DOI: 10.1074/jbc.274.34.23963
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Microsomal Epoxide Hydrolase Gene

Abstract: Microsomal epoxide hydrolase (mEH) is a conserved enzyme that is known to hydrolyze many drugs and carcinogens, and a few endogenous steroids and bile acids. mEH-null mice were produced and found to be fertile and have no phenotypic abnormalities thus indicating that mEH is not critical for reproduction and physiological homeostasis. mEH has also been implicated in participating in the metabolic activation of polycyclic aromatic hydrocarbon carcinogens. Embryonic fibroblast derived from the mEH-null mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(61 citation statements)
references
References 39 publications
0
61
0
Order By: Relevance
“…When 295-and 62-bp fragments appeared, the patient had homozygous allele of His139. When 174-, 121-and 62-bp bands appeared, the patient was identified as homozygous Arg139 allele, and when all four DNA fragments appeared, the patient was heterozygous with His139/Arg139 (1,(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…When 295-and 62-bp fragments appeared, the patient had homozygous allele of His139. When 174-, 121-and 62-bp bands appeared, the patient was identified as homozygous Arg139 allele, and when all four DNA fragments appeared, the patient was heterozygous with His139/Arg139 (1,(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…Epoxide hydrolase (EH) is a phase I biotransformation enzyme that catabolizes epoxides, which are converted from hydrophorbic polycyclic aromatic hydrocarbons (PAH), into dihydrodiols (1)(2)(3). In contrast to highly reactive epoxides, dihydrodiols are mostly inert and can be excreted after conjugating to glutathione (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that the interaction between these genes and environmental factors may also affect the susceptibility to leukemia [10]- [12]. Microsomal epoxide hydrolase (EPHX1), along with CYP, another family of xenobiotic-metabolizing enzymes, plays an important role in both the detoxification and activation of procarcinogens [13] [14] and is considered to be a protective enzyme [15]. Two polymorphisms in EPHX1, Tyr113 His in exon 3 (rs1051740) and His139Arg in exon 4 (rs2234922), have been identified to affect enzyme activity.…”
Section: Introductionmentioning
confidence: 99%